Influence of low contents of superhydrophilic MWCNT on the properties and cell viability of electrospun poly (butylene adipate-co-terephthalate) fibers - Rodrigues, Bruno V.M.; Silva, Aline S.; Melo, Gabriela F.S. [UNESP]; Vasconscellos, Luana M.R. [UNESP]; Marciano, Fernanda R.; Lobo, Anderson O. (Elsevier, 2016)
The use of poly (butylene adipate-co-terephthalate) (PBAT) in tissue engineering, more specifically in bone regeneration, has been underexplored to date due to its poor mechanical resistance. In order to overcome this drawback, this investigation presents an approach into the preparation of electrospun nanocomposite fibers from PBAT and low contents of superhydrophilic multi-walled carbon nanotubes (sMWCNT) (0.1-0.5 wt.%) as reinforcing agent. We employed a wide range of characterization techniques to evaluate the properties of the resulting electrospun nanocomposites, including Field Emission Scanning Electronic Microscopy (FE-SEM), Transmission Electronic Microscopy (TEM), tensile tests, contact angle measurements (CA) and biological assays. FE-SEM micrographs showed that while the addition of sMWCNT increased the presence of beads on the electrospun fibers' surfaces, the increase of the neat charge density due to their presence reduced the fibers' average diameter. The tensile test results pointed that sMWCNT acted as reinforcement in the PBAT electrospun matrix, enhancing its tensile strength (from 1.3 to 3.6 MPa with addition of 0.5 wt.% of sMWCNT) and leading to stiffer materials (lower elongation at break). An evaluation using MG63 cells revealed cell attachment into the biomaterials and that all samples were viable for biomedical applications, once no cytotoxic effect was observed. MG-63 cells osteogenic differentiation, measured by ALP activity, showed that mineralized nodules formation was increased in PBAT/0.5%CNTs when compared to control group (cells). This investigation demonstrated a feasible novel approach for producing electrospun nanocomposites from PBAT and sMWCNT with enhanced mechanical properties and adequate cell viability levels, which allows for a wide range of biomedical applications for these materials.
Keywords: Electrospinning; Mechanical properties, osteogenesis; Nanocomposites; PBAT; Superhydrophilic MWCNT